Role of propylene carbonate chirality on physicochemical properties of the corresponding ion conductors. (1st September 2015) - Jankowski, P.; Grzegorzewska, K.; Szabłowska, A.; Piszcz, M.; Dranka, M.; Żukowska, G.Z.; Kalita, M.
Highlights: The properties of the propylene carbonate-lithium triflate electrolytes were studied. The role of the enantiomeric purity of the solvent was discussed. Enantiomerically pure PC tends to form crystalline phase, racemic PC- glassy solid. The structure of the [PC]1 (NaCF3 SO3 )2 was determined by means of X-ray diffractometry. Several allotropic forms of PC were identified during spectroscopic studies. Abstract: The properties of the lithium triflate-propylene carbonate of various enantiomeric purity solid and liquid systems were investigated. Properties of the solutions were studied by means of vibrational spectroscopy (supported by X-ray data for sodium triflate as a base of the analysis of the spectra of the lithium triflate-propylene carbonate electrolytes) and impedance spectroscopy (conductivity). Thermal properties of the obtained electrolytes were studied by means of DSC. The main impact was put on ability of the system to the crystallization. These studies show that in the systems of higher enantiomeric purity and lower salt concentration, crystallization of the solvent is more pronounced (higher enthalpy of melting is observed). The use of enantiomerically pure solvents leads to the conductivity enhancement up to 15%. As the crystallinity of the system is higher for enantiomerically-pure systems, the conductivity increase may be ascribed to the organization of the electrolyte.